Trade Policy and Evolution of the External Sector in Colombia1970-2016 - Gallardo Sanchez, Carlos Felipe; Vallejo Zamudio, Luis Eudoro (Universidad Pedagógica y Tecnológica de Colombia, 2019)
The Colombian economy has witnessed an increase in commercial relations with the world. Regardless of the form, a country exercises a commercial policy whenever it intervenes to correct market imperfections. The article aims to describe the politics and evolution of the Colombian external sector for the period 1970-2016. Under a descriptive-analytical methodology and a quantitative approach, the collection, selection, analysis and interpretation of secondary sources is performed. It is found that the country has increased its commercial volume during the whole period, however, in 33 of the 47 years of study it incurs in a trade deficit. The policy instruments implemented have been liberalizing the national economy, but there is still a low diversification and dependence on traditional exports. Colombian trade policy is largely reactive and has operated to cope with coffee and oil bonanzas or currency availability, contrary to a long-term planning approach.